Into the unknown: A critical reflection on a truly global learning experience - Wolf, Katharina; Archer, Catherine (Western Australian Institute for Educational Research Inc, 2013)
Over the past decade, industry relevance and connectedness have evolved into a key requirement for students and their parents, who increasingly perceive employability upon graduation as a critical factor in the degree selection process. Simultaneously, professional bodies emphasise the need for high levels of industry engagement as a condition for accreditation, which in turn further impacts on the 'marketability' of a specific degree. However, many of the skills emphasised by potential employers and industry reference groups are more closely aligned with generic graduate attributes, rather than discipline specific knowledge and skills. This increasingly includes an emphasis on cultural awareness, excellent communication skills and the ability to work in dispersed, often even virtual teams. This observation is arguably particularly relevant within the business (degree) context, where workforces become increasingly multicultural, as traditional borders and limitations make way for transnational opportunities. This paper discusses the benefits and challenges associated with a third year student project that set out to combine the need for discipline specific knowledge, with the acquisition of versatile, culturally sensitive business skills. Students participating in the aptly titled 'communications challenge' competed against their peers as part of multicultural teams, representing twelve countries, across five continents. The authors conclude that experiential learning opportunities like this global, real life client project may not necessarily be popular amongst the wider student cohort. Furthermore, the acquisition of discipline specific knowledge may be limited when compared to 'traditional' teaching deliveries. However, projects like this provide a number of benefits, in particular in the context of capstone units that set out to prepare students for a diverse career in an increasingly global, multicultural and complex environment. © 2013 Issues In Educational Research.